2020
DOI: 10.3390/foods9091262
|View full text |Cite
|
Sign up to set email alerts
|

Podravka and Slavonka Varieties of Pepper Seeds (Capsicum annuum L.) as a New Source of Highly Nutritional Edible Oil

Abstract: The aim of this study was to evaluate Croatian pepper seed varieties (Podravka and Slavonka) as a new source of added value ingredients. Pepper seed is mostly considered a by-product. For the first time, the pepper (Capsicum annuum L.) seeds of the Slavonka and Podravka varieties were examined as the source material for oil production by the two methods of extraction: cold pressing (CP) and supercritical CO2 extraction (SC-CO2). Further, fatty acid profile, tocopherols, and sensory analysis of the oils were ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 18 publications
(33 citation statements)
references
References 40 publications
0
32
1
Order By: Relevance
“…In a recently published paper [ 9 ], pepper seeds, originating from the Croatian pepper varieties Podravka and Slavonka , were evaluated as new sources of high-value ingredients. Pepper seed oil obtained by cold pressing showed potential for culinary usage, and its nutritional quality can be compared to more expensive vegetable oils on the market.…”
Section: Introductionmentioning
confidence: 99%
“…In a recently published paper [ 9 ], pepper seeds, originating from the Croatian pepper varieties Podravka and Slavonka , were evaluated as new sources of high-value ingredients. Pepper seed oil obtained by cold pressing showed potential for culinary usage, and its nutritional quality can be compared to more expensive vegetable oils on the market.…”
Section: Introductionmentioning
confidence: 99%
“…Their effect in the treatment of painful conditions has been evaluated, such as rheumatic diseases [66]. Many recent studies have shown the effective treatment of capsaicinoïds for several sensory nerve fiber disorders, including arthritis and human immunodeficiency virus [67]. In this context, the proposed diet rich in pepper fruits can be considered an excellent strategy to improve the nutritional value of the population due to its high antioxidants and phenolic compound content.…”
Section: Antioxidants In Pepper Fruitsmentioning
confidence: 99%
“…They are recognized for their antimicrobial, anticarcinogenic and antioxidant effects (Chouaibi et al, 2019). Pepper seed has a high percentage of dietary fiber and is a good source of protein and fatty acids (El-Safy et al, 2012, Cvetković et al, 2020. The oil content in pepper seeds is above 20%, which means that it is promising for new products such oils and the products thereof.…”
Section: Nutritional Characteristics Of the Pepper By-productsmentioning
confidence: 99%
“…The oil content in pepper seeds is above 20%, which means that it is promising for new products such oils and the products thereof. Red pepper seed oils are rich in polyunsaturated fatty acids, especially linoleic acids (Yılmaz et al, 2015, Koncsek et al, 2018, Cvetković et al, 2020. Linoleic acid and α-linolenic acid have been recognized as essential fatty acids and are precursors of other important fatty acids in metabolism (Chouaibi et al, 2019).…”
Section: Nutritional Characteristics Of the Pepper By-productsmentioning
confidence: 99%